Port-city relation on contemporary Lisbon: the articulator role of public space - Ochoa, R. (PORTUSplus, 2012)
The changes that have been taking place, recently, in waterfronts, refer to the study of port cities, to their specificities and to the dynamics of their territories. This paper proposes an analysis of the relationship between the inner city and the waterfront on contemporary Lisbon, by means of the urban structures that connect these two realities – the transversal axes –, called structures of articulation with the waterfront. In this territorial system, the public space plays an important role, because of its articulating properties. But this is also a symbolic system. The different ways of articulation are related with one key factor: the existence of public art in the transversal axes and in the proper waterfront. First, the paper focuses on the different aspects that contribute to characterize the articulation. Among these aspects, it focuses on those that are related with the uses of the space, such as the visibility of the waterfront, or the continuities and ruptures in the acess ways to the waterfront. Finally, the paper explores the characteristics of public art in port cities, its relation with the articulation and its potencial in urban regeneration.